Pilot-scale process development for low-cost production of a thermostable biodiesel refining enzyme in Escherichia coli - Eberhardt, Maria Florencia (2018)
Biodiesels produced from vegetable oils have a major quality problem due to the presence of steryl glucosides (SGs), which form precipitates that clog filters and cause engine failures. Recently, we described an enzymatic process for removing SGs from biodiesel. However, industrial adoption of this technology was hindered by the cost of the steryl glucosidase (SGase) enzyme used. Here we report the development and validation at the pilot scale of a cost-efficient process for manufacturing the SGase. First, we tested various low-cost carbon sources for the Escherichia coli producing strain, ultimately developing a fed-batch fermentation process that utilizes crude glycerol as a feedstock. Next, we designed an efficient process for isolating the SGase. That process uses a novel thermolysis approach in the presence of a non-ionic detergent, centrifugation to separate the solids, and ultrafiltration to concentrate and formulate the final product. Our cost analysis indicates that on a large scale, the dose of enzyme required to eliminate SGs from each ton of biodiesel will have a manufacturing cost below $1. The new process for manufacturing the SGase, which will lead to biodiesels of a higher quality, should contribute to facilitate the global adoption of this renewable fuel. Our technology could also be used to manufacture other thermostable proteins in E. coli.